2022
DOI: 10.1007/s12640-022-00534-2
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Exposure-Induced Changes in Brain Metabolome: Implications in the Pathogenesis of Neurodegenerative Disorders

Abstract: Pesticides have been used in agriculture, public health programs, and pharmaceuticals for many decades. Though pesticides primarily target pests by affecting their nervous system and causing other lethal effects, these chemical entities also exert toxic effects in inadvertently exposed humans through inhalation or ingestion. Mounting pieces of evidence from cellular, animal, and clinical studies indicate that pesticide-exposed models display metabolite alterations of pathways involved in neurodegenerative dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…Among the alterations found in the metabolism of amino acids, the authors cited a decrease in tyrosine in the studied group, which consequently generated a decrease in dopamine, causing Parkinson’s disease in the exposed insects. Rodrigues et al [ 51 ] also detected tyrosine levels reduced by exposure to pesticides in neuronal cells and correlated changes in amino acid levels with neurodegenerative conditions in patients with Alzheimer’s disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the alterations found in the metabolism of amino acids, the authors cited a decrease in tyrosine in the studied group, which consequently generated a decrease in dopamine, causing Parkinson’s disease in the exposed insects. Rodrigues et al [ 51 ] also detected tyrosine levels reduced by exposure to pesticides in neuronal cells and correlated changes in amino acid levels with neurodegenerative conditions in patients with Alzheimer’s disease.…”
Section: Resultsmentioning
confidence: 99%
“…Its metabolism involves two enzymes: glutamine synthase, which is related to the synthesis of glutamine, and glutaminase, which acts in its conversion into glutamate, the latter being an important amino acid in cell metabolism that can be converted into gamma-aminobutyric acid (GABA), glucose, urea, synthesis of other amino acids or glutathione. Studies claim that negatively regulated glutamate uptake can contribute to the accumulation of glutamate in the synaptic cleft, causing a neurodegenerative process called excitotoxicity [ 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their multifactorial origin, their various causative mechanism is largely unexplored, except in cases where the basis is familial. Studies have shown that environmental exposure to neurotoxicants can alter several metabolite levels in the brain and induce neurodegeneration (Rodrigues et al 2022). Radiation exposures have been linked to the triggering of sporadic cases of neurodegeneration through the accumulation of chronic damage over the early years and manifesting as disease during old age (Sharma et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these etiological factors, xenobiotics such as pesticides and ionizing radiation (IR) are at the forefront, mainly due to their increasing application (Walther et al 2023 ). Pesticides have been linked to neurodegeneration through oxidative stress, mitochondrial dysfunction, DNA damage and altered cellular signalling (Narasimhamurthy et al 2022a ; Rodrigues et al 2022 ; Prathiksha et al 2023 ), while IR has also been studied for their role in inducing neurotoxicity (Sharma et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%